Enfants du hasard - Michel, Thierry, ....-; Colson, Pascal, ....- ([s.l.] : Twin Pics / Passerelle, 2017)
In the small local school of Cheratte, a former mining town, 11-year old students with and immigrant background are coming to the end of their primary school education with Brigitte. She is a dynamic teacher whose particular pedagogical approach aims to give these pupils a firm foundation to build on in this constantly changing world. Throughout the school year, the film follows these children, grandsons of miners, mainly Turks and Muslims. While some of their elders opt for identity closure, this film evokes the challenge awaiting these children to integrate into current society, in the face of terrorist attacks and harassment via social media. This documentary record is an ode to life. It captures the children's spontaneity,their joy of living, the end of childhood. The children's voices gradually weave the links between past, present and future.
Thema-dvd - Dans la petite école communale d'une ancienne cité minière, des élèves issus de l'immigration terminent leur cycle d'études primaires avec Brigitte, une institutrice dont l'enthousiasme bienveillant prépare ces écoliers à s'épanouir dans un monde en mutation. Le film suit le parcours scolaire de ces petits-enfants de mineurs, majoritairement musulmans et la plupart d'origine turque. Alors que certains de leurs aînés font le choix d'un repli identitaire, ce film met en lumière la manière dont les enfants cherchent à se construire et à donner un sens à leur vie. Il saisit leurs doutes et leurs réflexions lors des attentats terroristes et face au harcèlement sur les réseaux sociaux. Ode à la vie, narré par la voix des enfants, ce documentaire révèle surtout leurs espoirs et leur vision du futur. Il capte la spontanéité, le plaisir d'être, la fin d'un temps d'insouciance avec ses fragilités. Le film tisse ainsi les liens entre passé, présent et futur et dessine un sens du bonheur possible, au sein de l'école et de la société.
EAN : 5051083123792